2016
DOI: 10.4028/www.scientific.net/kem.685.380
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Quality of the Coating at Hot-Dip Galvanizing of Machine Steels in the Zinc Melt with Microadditives of Nickel

Abstract: The technology of microalloying zinc melt by nickel is widely used to control the thickness of the zinc coating when the machine steels are subject to hot-dip galvanization. However, in some cases inclusions of Ni-Zn-Fe dross are formed on surface of the products, which leads to their deterioration. The aim of this work is to investigate the microstructure, mechanism of formation and elemental composition of this dross. Conditions for the formation of different phases in the coating were analyzed using Ni-Zn-F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Nickel and Tin-Antimony are conventional chemical composition of the coating which is generally used for brass alloys. Previous studies demonstrated that the quality of the coating, especially in the hot-dipping technique, is directly related to the process parameters [11,14,15]. An appropriate coating should guarantee the free from defect, excellent adhesion and uniformity of thickness.…”
Section: Introductionmentioning
confidence: 99%
“…Nickel and Tin-Antimony are conventional chemical composition of the coating which is generally used for brass alloys. Previous studies demonstrated that the quality of the coating, especially in the hot-dipping technique, is directly related to the process parameters [11,14,15]. An appropriate coating should guarantee the free from defect, excellent adhesion and uniformity of thickness.…”
Section: Introductionmentioning
confidence: 99%
“…However, at a nickel concentration of 0.06-0.09%, the floating dross formation is observed; it settles on the product and leads to defects in the coating surface [9]. Dross formation is due to the fact that the solubility limit of nickel in zinc with iron impurity at 450°C is 0.06% [10][11][12]. Chinese researchers note that a nickel concentration of 0.05% is effective and provides a reduction in coating thickness on Q235 steel (Si = 0.15%) [13].…”
Section: Introductionmentioning
confidence: 99%
“…Very little research on high-temperature galvanizing has been done. It was mainly performed abroad [7][8][9]. The main aim of this work is to study the influence of elevated temperatures of hot-dip galvanizing on the thickness and microstructure of zinc coatings on fixing products and elaborate recommendations for optimal technological parameters of hot-dip galvanizing.…”
mentioning
confidence: 99%